Refining the excretion factors of methadone and codeine for wastewater analysis — Combining data from pharmacokinetic and wastewater studies. (September 2016) - Thai, Phong K.; Lai, Foon Yin; Bruno, Raimondo; van Dyken, Emma; Hall, Wayne; O'Brien, Jake; Prichard, Jeremy; Mueller, Jochen F.
Abstract: Analysing drug residues in wastewater (wastewater analysis) to monitor the consumption of those drugs in the population has become a complementary method to epidemiological surveys. In this method, the excretion factor of a drug (or the percentage of drug metabolites excreted through urine) is a critical parameter for the back-estimation of the consumption of a drug. However, this parameter is usually derived from a small database of human pharmacokinetic studies. This is true for methadone and codeine, the two most commonly used opioids and also common substances of abuse. Therefore, we aimed to refine the current excretion factors used for estimating methadone and codeine by analysing published data from the literature on the excretion of methadone, its main metabolite, 2-ethylidene-1, 5-dimethyl-3, 3-diphenylpyrrolidine (EDDP), and codeine. Our review included both human drug pharmacokinetic studies and wastewater analysis studies. We found that while the commonly used excretion factor of methadone (~ 27.5%) was relatively accurate, the excretion factor of EDDP, a better biomarker for methadone consumption in sewer epidemiology, should be twice that of methadone (i.e. 55%) instead of the current equal or half values. For codeine, the excretion factor should be ~ 30% instead of 63.5% or 10% as previously used in wastewater analysis studies. Data from wastewater analysis studies could be used in this way to refine the excretion factors of the drugs of interest. Highlights: It is an extensive review to refine the excretion factors for methadone and codeine. It is the first study to utilize urine testing and wastewater data in the refining process. Currently used excretion factors of EDDP and codeine were probably not appropriate. New excretion factors were proposed for EDDP and codeine. Controlled wastewater analysis studies are useful for refining excretion factors.